English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-01-11 12:03:07 · 3 answers · asked by cobra 1 in Science & Mathematics Mathematics

3 answers

(x-1)*(x-1) x^2 - 2x + 1, so x = 1 is the solution!

2007-01-11 12:06:46 · answer #1 · answered by firefly 6 · 0 0

if it is (x^-2)x+1=0, then you can change it to
(1/x^2)x+1=0
x/x^2+1=0
1/x=1
1=x.
if it is quadratic, and is x^2-2x+1=0
factor to
(x-1)(x-1)=+/- 0
x-1=0 or x-1=0
x=1 or x=1
No matter what, x=0.

2007-01-11 20:13:27 · answer #2 · answered by Brandon B 2 · 0 0

x^2-2x+1=0
(x-1)(x-1)=0
x-1=0
x=1

2007-01-11 20:07:30 · answer #3 · answered by Antonio R 3 · 0 0

fedest.com, questions and answers